Induction and Its Relevance to the Transformation of Sharia Economic Law in Indonesia: A Study of Four Madhhabs - Enang Hidayat (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2023)
This research aims to determine the existence and urgency of induction in the methodology of Islamic law of the four schools of jurisprudence and its relevance to the transformation of Sharia economic law in Indonesia. This study falls under the category of normative Islamic legal research using a conceptual and philosophical approach. Primary data is sourced from the foundational books of Islamic jurisprudence of the four schools: "al-Mahsul" by Al-Razi (Shafi'i), "Syarh Tanqih al-Fusul" and "al-Furuq" by Al-Qurafi (Maliki), "Taqrib al-Usul" by Ibn Juzay (Hanbali), and "Al-Muwafaqat" by Al-Shatibi (Maliki). The data is analyzed comparatively and prescriptively using inductive logic and reasoning. The research demonstrates that the existence of induction in the methodology of Islamic law among the four schools is most prominent as Islamic legal inference (istidlal). The urgency of induction as a methodology in Islamic law is relevant to efforts to transform Sharia economic law within Indonesian law. There are four principles of jurisprudence as products of Islamic thought influenced by inductive logic, which legitimize the fatwas of the National Sharia Board of the Indonesian Ulema Council (DSN-MUI), such as Fatwa No. 135/DSN-MUI/V/2020 on Shares, Fatwa No. 116/DSN-MUI/IX/2017 on Sharia Electronic Money, Law No. 41 of 2004 on Endowments, Article 16 paragraph (3) concerning endowed property such as money, and Supreme Court Regulation No. 2 of 2008 on the Compilation of Sharia Economic Law, Articles 112-115 (Book II) regulating Bai al-Wafa. This research can enhance understanding of inductive logic in Islamic law within Islamic higher education institutions as well as for Sharia Courts and the fatwas of the DSN-MUI.